Descartes Puzzle: Intelligent Solitary Search for Truth and Epistolary Dialogues. - Mamali, Cătălin (International Journal of Interdisciplinary Cultural Studies, 2016)
Descartes' epistemology that posits the methodic doubt and solitary search for truth seems to collide -with the social-cognitive character of his correspondence that practices dialogue, inter-subjective reasoning, and testing among equal inquiring partners. "Descartes' Puzzle" has at its core the tension between an epistemically solitary search for truth and the social nature of the epistolary dialogue in -which he has been involved during the stages of his intellectual life that also included many face-to-face conversations. Descartes' conception on the rules of mind, on systematic doubt, and the search for truth that guide the solitary reasoning process on one side and the major features of his epistolary dialogue with others, i.e., an explicit social-cognitive interaction that implies inter-subjective reasoning and testing among equals on the other side, form a dynamic inquiring system. The paper presents some of the major traits of an integrative approach of epistolary interaction that takes into account its structural patterns (within each epistolary and between the senders and receivers), the cycles of epistolary exchanges, the epistolary volume, its degree of reciprocity, and the epistolary meta-messages (on letters safety, on correspondence channels, on the content of letters) as these indicators have been worked out as part of "correspondentometry" (Mamali 1985, 1990, 1992). The empirical study, based on Cartesius' correspondence, strongly suggests that during all the periods, usually right after the completion of a work that marked highly significant intellectual achievements, the epistolary interactions of Descartes increased tremendously. This pattern supports the hypothesis that his need for inter-subjective testing, for dialogue with the other on specific inquiring issues has been present even during his solitary work, at least latently. Additionally, it increased markedly and explicitly during periods of high intellectual achievements. The patterns of epistolary interactions suggest that along his intellectual life Descartes reversedfrequently from a relatively solitary mode of inquiry toward a complex inter-subjective dialogue -with various partners. The meaning of these reversals, that are themselves part of a wider dialogical context, are discussed both from epistemic and social perspectives underscoring that Descartes highly valued the social-cognitive interactions among inquiring individuals.